Emergence of the Stoner-Wohlfarth astroid in thin films at dynamic regime. Issue 1 (December 2017) - Cuñado, José; Bollero, Alberto; Pérez-Castañeda, Tomás; Perna, Paolo; Ajejas, Fernando; Pedrosa, Javier; Gudín, Adrian; Maldonado, Ana; Niño, Miguel; Guerrero, Rubén; Cabrera, David; Terán, Francisco; et al.
Abstract The Stoner-Wohlfarth (SW) model is the simplest model that describes adequately the magnetization reversal of nanoscale systems that are small enough to contain single magnetic domains. However for larger sizes where multi-domain effects are present, e.g., in thin films, this simple macrospin approximation fails and the experimental critical curve, referred as SW astroid, is far from its predictions. Here we show that this discrepancy could vanish also in extended system. We present a detailed angular-dependent study of magnetization reversal dynamics of a thin film with well-defined uniaxial magnetic anisotropy, performed over 9 decades of applied field sweep rate (dH /dt ). The angular-dependent properties display a gradual transition from domain wall pinning and motion-like behaviour to a nucleative single-particle one, as dH /dt increases. Remarkably, in the high dynamic regime, where nucleation of reversed domains is the dominant mechanism of the magnetization reversal (nucleative regime), the magnetic properties including the astroid become closer to the ones predicted by SW model. The results also show why the SW model can successfully describe other extended systems that present nucleative regime, even in quasi-static conditions.